Religion and spirituality in coping with advanced breast cancer: perspectives from Malaysian Muslim women - Ahmad, Farizah; Muhammad, Mazanah; Abdullah, Amini Amir (Springer, 2011)
This article is part of a larger study on the role of spirituality in coping with breast cancer among Malaysian Muslim women. The study seeks to reveal the meaning of the experience through the stories of three Muslim women surviving advanced breast cancer, to better understand the deep meanings that inform their experiences with spirituality and transformation as they cope with the challenges of breast cancer. Data were gathered using in-depth interview. Qualitative methods were used in identifying two themes—illness as an awakening and hope and freedom comes from surrendering to God. The themes were discussed in the context of two broad areas: (1) what are the new meanings these women discovered in their experiences with cancer; and (2) how did the new meanings change their lives? The study suggests that cancer survivors’ experiences with cancer and their learning processes must be understood within the appropriate cultural context. This is especially so for spirituality. The common emphasis of spirituality on relationship with God, self and others, may significantly influence how people learn to live with cancer.